Bioethics and biotechnology: the human between two paradigms - Roland Schramm, Fermín; Kottow Lang, Miguel (Acta Bioethica, 2001)
This paper intends to analyse some of the interactions that occur between biotechnology and bioethics, considering that both disciplines have a truly paradigmatic character that influences the anthropologic views of modern man and future human generations. We suggest that biotechnology, especially in the form of genetic interventions, questions certain anthropologic constants and must therefore be subjected to descriptive and prescriptive bioethical reflection. Benefit/risk ratios must be analyzed from the social and the ethical points of view, effective decisional mechanisms need to be suggested, and prudential regulation will have to be envisioned as well as the promotion of equity in the access to biotechnologic benefits.